25d+25.4=

Simple and best practice solution for 25d+25.4= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 25d+25.4= equation:


Simplifying
25d + 25.4 = 0

Reorder the terms:
25.4 + 25d = 0

Solving
25.4 + 25d = 0

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-25.4' to each side of the equation.
25.4 + -25.4 + 25d = 0 + -25.4

Combine like terms: 25.4 + -25.4 = 0.0
0.0 + 25d = 0 + -25.4
25d = 0 + -25.4

Combine like terms: 0 + -25.4 = -25.4
25d = -25.4

Divide each side by '25'.
d = -1.016

Simplifying
d = -1.016

See similar equations:

| 3.6t+4.93=-30.71 | | 39+6=99+8 | | -27=8m-5m | | 4000=1920*x*8 | | 2m+2.6= | | 1.4m+9.91=-0.87 | | 24x-94=x-10 | | -9r+10=8+3r | | 10-5(9n-9)=10 | | 4x^2-x-29=0 | | 5/20=9/x | | 18a^2-48a+32=0 | | x+-5=2x+1 | | -3(2x+7)=-6x-21 | | 1.5(m-3)=12 | | 2x+y=3.5 | | 3secx-5=-8 | | 3(2p+1)=7(-p)-6 | | x^2-4x^1+3=0 | | 3.4c-17=68 | | 9y=-x+9 | | -28(z-73)=z+6 | | 13x+5y=17 | | 6x+4x+4+8=5x+3+4x | | 4a^2+19a+12=0 | | (7.1)1.9= | | -2y+3=-9 | | -2y+3=-8 | | 5g+4(-8+5g)=1-g | | 74y-4884=y+(-72) | | 74y-4884=y+(-74) | | A-10=34 |

Equations solver categories